Cultural Intelligence, Communication Effectiveness, Global Leadership, and Organizational Effectiveness: Insights from the Indian Hospitality Sector - Resho, Resho; Singh, Netra Pal (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
The increasing globalization of business operations has heightened the need for leaders capable of navigating culturally diverse environments. This study explores the interrelationships between cultural intelligence (CQ), communication effectiveness, global leadership, and organizational effectiveness within the context of India’s hospitality sector. This research examines how these constructs interact to influence organizational outcomes by using exploratory and confirmatory factor analyses (EFA and CFA) and structural equation modeling (SEM). Data collected from 360 managers working in various sub-sectors of the hospitality industry reveal significant positive relationships between the constructs. The findings emphasize the importance of CQ as a foundational competency for communication effectiveness and global leadership, which collectively enhance organizational performance. This paper contributes to the growing discourse on leadership in multicultural and emerging market contexts, offering practical insights for organizations and policymakers.